From the Basque provinces and Navarre to Chihuahua: immigration, networks to the place of birth and political participation in 18th Century - Mendoza-Flores, Hugo (Huarte de San Juan. Geografía e Historia, 2020)
This paper aims to contribute to the study of Alava, Gipuzkoa, Navarre and Biscay native’s political participation in a northern villa of New Spain; in the municipal council as well as in other corporations operating in town. Understanding them as migrants, both the linkages with the country they chose to live in and those with the place where they were born will be analysed. This research is based on primary sources from the Municipal Archive and the Archiepiscopal Archive of Chihuahua, in Mexico; archives in Spain consulted by the PARES website and genealogical databases. Instead of offering closed conclusions, this work aims to encourage future investigations